The Turkey, Russia, Iran Nexus: Evolving Power Dynamics in the Middle East, the Caucasus, and Central Asia - Brannen, Samuel (Rowman & Littlefield Publishers, 2013)
This report is the culmination of a two-year project examining the complex relations among Turkey, Russia, and Iran in an effort to better understand these countries’ perceptions in the post-Cold War world and the conditions and interests that cause international political alignments among them. It surveys the undercurrents of these relationships in a political, economic, and energy supply and demand context and assesses the geostrategic and regional impact of these dynamics through a series of case studies on developments in the Middle East, Caucasus, and Central Asia. The report is meant to provide U.S. policymakers with practical recommendations for calibrating and balancing relations with each of these three countries, while taking into account the interests of other major actors. It integrates independent analysis by CSIS scholars with perspectives from Turkish, Russian, and Iranian counterparts obtained through extensive field research and two international workshops held in Ankara and Moscow.